The Influence of Leadership Style and Motivation on Employee Performance at SMP Negeri 46 Jakarta - Bambang Harmoko; Swasta Bangun (International Journal of Management and Business Economics, 2024)
The purpose of this research is to determine the influence of Leadership Style and Motivation on Employee Performance at SMP Negeri 46 Jakarta using a research sample of 38 employees with data analysis techniques using multiple regression analysis. The research results show an R Square value of 0.633, meaning that Leadership Style (X1) has a significant effect on Employee Performance (Y) by 63.3%, while the remaining 36.7% is caused by the influence of other factors that were not studied. The R Square value of 0.701 means that Motivation (X2) has a significant effect on Employee Performance (Y) by 70.1%, while the remaining 29.9% is caused by the influence of other factors that were not studied. The Adjusted R Square value of 0.813 means that Leadership Style (X1) and Motivation (X2) have a joint and significant effect on Employee Performance (Y) of 81.3%, while the remaining 18.7% is caused by the influence of other variables that are not examined in this research.